Utilization and responsiveness of the asthma control test (ACT) at the initiation of therapy for patients with asthma: a randomized controlled trial - Al Moamary Mohamed S; Al-Kordi Ahmed G; Al Ghobain Mohammed O; Tamim Hani M (BMC Pulmonary Medicine, 2012)
Abstract Background The aim of this study was to assess the responsiveness of the asthma control test (ACT) to detect changes at the initiation of therapy and its utilization in the initiation of asthma treatment. Methods This study was designed as a randomized clinical trial conducted in a primary care setting. The subjects were asthma patients who had not received controller therapy for at least two months. The patients were randomized into two groups: The Saudi Initiative for Asthma (SINA) group and the Global Initiative for Asthma (GINA) group. Treatment in the SINA group was initiated at step1 when the ACT scores ≥ 20, step 2 when the score between16-19, and step 3 when the score < 16 began at step 3. The GINA group patients were started on step 2 when they had persistent asthma symptoms or step 3 when they had severely uncontrolled disease. Results Forty-five patients were analyzed in each group. The improvement in ACT score after treatment initiation was significantly higher when the SINA approach was used (2.9 in the SINA group compared to 1.7 in the GINA group (p = 0.04)). The improvement in FEV1 was 5.8% in the SINA group compared to 3.4% in the GINA group (p = 0.46). The number of patients who achieved asthma control at the follow-up visit and required no treatment adjustment was 33 (73.3%) in the SINA group and 27 (60%) in the GINA group (p = 0.0125). Conclusion The ACT was responsive to change at the initiation of asthma treatment and was useful for the initiation of asthma treatment. Trial Registration number ISRCTN31998214